2017
DOI: 10.1152/jn.00327.2017
|View full text |Cite
|
Sign up to set email alerts
|

A novel paraplegia model in awake behaving macaques

Abstract: Lower limb paralysis from spinal cord injury (SCI) or neurological disease carries a poor prognosis for recovery and remains a large societal burden. Neurophysiological and neuroprosthetic research have the potential to improve quality of life for these patients; however, the lack of an ethical and sustainable nonhuman primate model for paraplegia hinders their advancement. Therefore, our multidisciplinary team developed a way to induce temporary paralysis in awake behaving macaques by creating a fully implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Furthermore, a few contusive SCI studies have been carried out in large primates because they are difficult to handle, labor-intensive, and require indispensable skilled daily care (Babu and Namasivayam, 2008). In addition, weight-supported treadmill rehabilitation requires an extremely hard step of putting a weight support jacket on monkeys and some other special rehabilitative setups (Krucoff et al, 2017). On the other hand, small marmosets are easy to handle, care for, and rehabilitate (Okano, 2021).…”
Section: A Severe Contusion Model With Rehabilitation In Marmosetsmentioning
confidence: 99%
“…Furthermore, a few contusive SCI studies have been carried out in large primates because they are difficult to handle, labor-intensive, and require indispensable skilled daily care (Babu and Namasivayam, 2008). In addition, weight-supported treadmill rehabilitation requires an extremely hard step of putting a weight support jacket on monkeys and some other special rehabilitative setups (Krucoff et al, 2017). On the other hand, small marmosets are easy to handle, care for, and rehabilitate (Okano, 2021).…”
Section: A Severe Contusion Model With Rehabilitation In Marmosetsmentioning
confidence: 99%
“…For example, a comparison of epidural, subdural and intraspinal stimulation at dorsal and ventral locations on, or in, the cervical spinal cord of rhesus monkeys revealed that differences in selectivity and in the direct or indirect activation of motor neurons could be advantageous in different situations (eg, when facilitating endogenous movements versus directly activating muscle groups), and that this should be taken into account when designing neuroprostheses 32 . A newly developed primate model of paraplegia that can elicit temporary lower extremity paralysis may also be useful for neural interface development and optimisation of stimulating and recording parameters 33 . In rodent SCI models, kinematic feedback and multi-electrode epidural arrays have allowed real-time spatiotemporal neuromodulation of flexor and extensor activity during hindlimb stepping 23 , robotic interfaces have been combined with epidural and pharmacological stimulation of the spinal cord to restore hindlimb stepping 34 , and activity-based feedback has been used to trigger synchronised intraspinal microstimulation for improving forelimb function 35 .…”
Section: Experimental Advancesmentioning
confidence: 99%
“…A trocar was then introduced through the fascia just lateral to midline between the spinous processes and advanced so the tip just entered the epidural space. Epidural location was confirmed using a loss of resistance technique, fluoroscopic x-ray, and lack of cerebrospinal fluid (CSF) (34). Next, an 8-contact cylindrical percutaneous lead was introduced through the trocar and steered through dorsal epidural space to a target location in the mid-thoracic spine, or approximately across T8 (Supplementary Figure 1b).…”
Section: Primate Implant Surgery and Timelinementioning
confidence: 99%